Neuropsycholinguistic Links Between Procrastination and Prospective Memory - Zhuravlova, Olena; Zhuravlov, Oleksandr; Kozachuk, Nataliya; Volzhentseva, Iryna; Zasiekina, Larysa (East European Journal of Psycholinguistics, 2021)
The research objective is to examine the brain activity of individuals with different levels of procrastination. The study applies EEG data analysis with different levels of linguistic stimuli complexity (letter and semantic word), allowing to change the cognitive load and register the electrical activity of the cerebral cortex while performing tasks with two different stimuli: perceptual and semantic. We registered the electrical activity of the cerebral cortex in 20 individuals (18 females, 2 males) in the shielding lightproof testing room of the Laboratory of Age Neurophysiology at Lesya Ukrainka Volyn National University. This technique analyzes the dynamics of cortical electrogenesis identifies general patterns of local and spatial synchronization of biopotentials of the cerebral cortex. The findings indicate that the dynamics of cortical electrogenesis of prospective memory depends on linguistic stimuli complexity in procrastinators, associated with increased energy expenditure. Furthermore, the largest number of statistically significant intergroup differences in subjects with different levels of procrastination was found in the beta range of EEG, indicating the rhythm of activity. On the one hand, this rhythm of activity is dependent on the optimization of problem-solving. On the other, the increase in its power reflects cortical excitation and selective inhibition. Evidence consistently suggests that the complexity of the linguistic task increases the interaction of brain macrostructures in the anterior associative zone (fronto-central leads) in students with dilatory behaviour. In contrast, subjects without dilatory behaviour demonstrate only changes in spatial synchronization modulated according to the linguistic stimuli complexity.